Innovative Social Policies for Gender Equality at Work - Fox, E; Pascall, G; Warren, Tracey (School of Sociology and Social Policy, University of Nottingham [online], 2006)
The project asked about policies to support work-family reconciliation among low-waged women in England. How are low-waged women constrained in their choices by limited and fragmentary social policies? We identified innovative social policies available in the international arena around parental leave, child-care, and time that could promote work-family reconciliation, more continuous employment and better quality jobs among low-waged women in England. Would these policies be attractive and better meet their needs in reconciling paid work and family?